Quantitative assessment of prosocial behaviour and trends of transfusion transmitted infections among voluntary blood donors: a cross sectional study - Satti, Siva Balaji Reddy; B., Ravikumar; V., Vijayasanti; K., Amarender Reddy (International Journal Of Community Medicine And Public Health, 2017)
Background: Every country faces an ongoing challenge to collect blood from safe donors. Chronic blood shortages are common in developing countries. According to WHO Voluntary blood donation practices are encouraged to collect safe blood units. In India for donating the blood often they say prosocial reasons. The objectives of the present study was quantitative assessment of prosocial behaviour as well as trends of transfusion transmitted infections among (voluntary blood donors) VBD. Methods: Cross-sectional study carried out between 1st January 2016 to 31st august 2016, at the field practice area of Institute of preventive medicine (IPM), Narayanaguda, Telangana state, India. The total sample size estimated was 41,356 (by Census survey method). Among which 25,641(62%) were current donors and 15,715 (38%) lapsed donors likewise 35,980 males and 5,376 females were enrolled. Results: Among the participants majority (87%) were males compare to females (13%). out of 41,352 donors majority were current donors (62%) compare to lapsed donors (38%). Among current donors all the mean scores of prosocial behaviour components were high and The trends of All TTIs infection prevalence rates were declined progressively. Conclusions: Sustainable motivational levels may increase the frequency of blood donation and by encouraging VBDs one can reduce the TTIs.